2014
DOI: 10.1111/cod.12293
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐reactivity between citral and geraniol – can it be attributed to oxidized geraniol?

Abstract: There is little cross-reactivity between pure geraniol and citral; however, concomitant reactions to citral and oxidized geraniol were common, owing to geranial. Geranial was also the main sensitizer in the mixture citral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 36 publications
1
31
2
Order By: Relevance
“…An Eclipse Plus C 8 column (3.5 μm, 4.6 × 150 mm; Agilent Technologies) was used. Analysis of geranial, neral, and citral was conducted with external standards as previously described . All chemicals were distilled prior to use.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An Eclipse Plus C 8 column (3.5 μm, 4.6 × 150 mm; Agilent Technologies) was used. Analysis of geranial, neral, and citral was conducted with external standards as previously described . All chemicals were distilled prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…has been patch tested in a study at the University of Gothenburg, giving 0.92% positive reactions in 655 patients. In the same study, geranial and neral were tested 3.5% pet., yielding 2.0% and 0.92% positive reactions, respectively . Irritation was investigated before the study and found to be low; patch test concentrations were subsequently chosen according to guidelines …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patch test results showed that 19 of 655 tested persons reacted positive to one or more tested compounds. Out of these 19 patients, 13 reacted positive to geranial [103].…”
Section: Geraniolmentioning
confidence: 99%
“…Citral consists of a mixture of two isomers, geranial ( trans ‐citral or citral A) and neral ( cis ‐citral or citral B) (Rodov et al . ), both formed by oxidation and activation of geraniol (Hagvall & Christensson ), and is a major constituent in Cymbopogon citratus (where it represents 70–80% of total monoterpenes; Ganjewala et al . ), Melissa officinalis and Litsea cubeba essential oils (Rauber et al .…”
Section: Introductionmentioning
confidence: 99%